Analisis Penetapan Rencana Induk Pelabuhan Belawan Terhadap Kesejahteraan Masyarakat - Denny Setiawan Saputra; Sirojuzilam Sirojuzilam; Agus Purwoko (Fakultas Teknik, 2020)
The National Development Planning Agency (BAPPENAS) and Indonesia Transportation Ministry have established 2015-2019 National Mid-Term Development Plan (RPJMN) and Belawan Port Master Plan (RIP) 2012 (revised 2018). Central Statistics Agency (BPS) in 2017 National Socio-Economic Survey (SUSENAS) established several indicators of welfare, one of which is population. This study aims to describe relationship between 2015-2019 RPJMN and Belawan RIP 2012 (revised 2018) and illustrate impact development of Port of Belawan on surrounding community welfare. Quantitative-qualitative descriptive research was chosen with Secondary Data Analysis (ADS) approach and validated by triangulation method. research population is in Medan Belawan sub-district and sample uses times series design method and non-probability purposive sampling. Data were obtained from Bappenas, Transportation Department and PT. Pelabuhan Indonesia, Belawan RPJMN and RIP document and BPS Medan Municipality, namely population data. Population parameters are analysis results from several sub-parameters, namely population growth, population density, and migrant population. Study results successfully illustrated relationship between RPJMN and Belawan RIP and Belawan Port existence had a positive impact on development of surrounding communities’ welfare. This study results were validated using secondary data from Googlemap in form of a map of economic distribution activity and photographs of businesses.